Modelling and Control of Proposed Two Dodecacopter Systems - Şahin YILDIRIM; Nihat ÇABUK; Veli BAKIRCIOĞLU (International Journal of Applied Methods in Electronics and Computers, 2020)
Nowadays, the use of multi-propellers has been increased, because of some basic advantages such as vertical take-off and landing, simple mechanical structure. In addition, different usage fields such as carrying an object and making video records over the cities. This paper exposes design and control of two different multi propeller systems and both systems have 12 rotors to carry more load. In first, all motors are arranged at identical angles in the same plane. In the other, the motors are mounted in two groups, eight and four in two different planes, the lower and upper. Flight performances of these two different UAVs were compared under disturbing effect. It was observed that the flight performances were close in the simulation study. Although the average and maximum of the position errors for three axes in the first model was less than the other, for the same propeller dimensions, the first model must have larger dimensions than the other in the context of the smallest vehicle dimensions.